2023
DOI: 10.1177/02692163231152526
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of healthcare utilization and life-sustaining interventions between patients with glioblastoma receiving palliative care or not: A population-based study

Abstract: Background: Palliative care has historically been under-utilized in patients with glioblastoma. Furthermore, literature on the utilization of healthcare and life-sustaining interventions during the late-stage of glioblastoma has been limited. Aim: To identify and compare healthcare utilization and life-sustaining interventions between patients with glioblastoma who received palliative care and who did not based on patients identified retrospectively from Taiwan Cancer Registry between January 2007 and December… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The authors reported that 34% of patients received palliative care. They further found that the survival of these patients who did receive palliative care was significantly longer than that of those who did not receive palliative care [71]. The results of this retrospective study need to be treated with caution, as individuals who live longer would have had more time to have palliative care services organized, which might explain why they received palliative care more often.…”
Section: Palliative Carementioning
confidence: 84%
See 1 more Smart Citation
“…The authors reported that 34% of patients received palliative care. They further found that the survival of these patients who did receive palliative care was significantly longer than that of those who did not receive palliative care [71]. The results of this retrospective study need to be treated with caution, as individuals who live longer would have had more time to have palliative care services organized, which might explain why they received palliative care more often.…”
Section: Palliative Carementioning
confidence: 84%
“…Despite both the European Association of Neuro-Oncology (EANO) [3] and the National Institute for Health and Clinical Excellence (NICE) [69] recommending early referral to palliative and supportive care services, the actual provision of such care to people with primary brain tumors is scarce [70]. Recently, Shieh et al [71] conducted a large population-based retrospective analysis (n = 1994) of the utilization of palliative care in patients with glioblastoma in Taiwan over a period of ten years. The authors reported that 34% of patients received palliative care.…”
Section: Palliative Carementioning
confidence: 99%
“…In the other paper, Shieh et al compared healthcare utilization and life-sustaining interventions between patients with glioblastoma who received palliative care and who did not receive palliative care, based on patients identified retrospectively from the Taiwan Cancer Registry. 3 They found, amongst others that patients with glioblastoma who received palliative care had longer survival although less frequently invasive interventions were given. They also found that only about 34% of patients with glioblastoma were referred to palliative care within 1 year of death, based on claims submitted to the National Health Insurance.…”
mentioning
confidence: 99%